Extreme El Niño Events - Dewitte, Boris (2019)
Every few years the tropical Pacific warms abnormally in association with a relaxation of the trade winds, a phenomenon known as the El Niño–Southern Oscillation (ENSO) that represents the strongest fluctuation of the global climate system. Although the contemporary observational record indicates that all El Niño events are not alike, differing in amplitude, warming pattern, and teleconnection, there is a class of events that stands out in terms of the societal and economical impacts: the extreme El Niño events that have occurred every 15–20 years. In this chapter, we propose an overview of the state of knowledge and of some current lines of research dedicated to extreme El Niño events. Building on the recently proposed concept of ENSO diversity, we further synthesize our current understanding of the nonlinear dynamics of this class of events and their expected evolution in a warmer climate and highlight some challenges in ENSO research.